Coordenadoria Integrada de Operações Aéreas – CIOPAER: uma nova proposta de estrutura de atuação na segurança pública no Estado do Ceará - Veras, Alan Menezes (2024)
This work presented the importance of the public aviation service in the State of Ceará, presenting the relevant activities and the different forms of operation of the aircraft of the Integrated Coordination of Air Operations – CIOPAER, which uses public air transport as support. The importance of aerial activity in public safety in the State of Ceará is extremely relevant. The Integrated Air Operations Coordination - CIOPAER is a body that plays an important role in the State's public security. CIOPAER currently operates in five regions of the State, including: Fortaleza, Sobral, Juazeiro, Crateús and Quixadá. This body performs multimission activities, such as: police operations, air patrolling, rescue services, aeromedical services, civil defense actions, organ transport, environmental monitoring, fire fighting, land and water search and rescue, pre-hospital care, authority transport among others. Currently, to carry out all these activities the operational cost of the current operating structure in 2022 was approximately R$7,720,870.40 while from January to August 2023 it was approximately R$5,165,629.37. When considering the maintenance cost of aircraft in this system, there will be an increase of approximately R$ 15,948,166.10 in 2022 and R$ 10,546,858.97 from January to August 2023. The main objective of this Dissertation is to propose a new operating structure for CIOPAER with the opening of a base in the Jaguaribe and Center-South regions, reducing its operating cost by around R$715,214.54 comparing the years 2022 and from January to August 2023. It is also proposed to transfer the CIOPAER base from the municipality of Quixadá to the municipality of Quixeramobim, thus reducing its operating cost by around R$ 61,222.73 in the same period. Additionally, a new maintenance system for CIOPAER aircraft is proposed, which will reduce its cost by approximately R$ 982,696.12 compared to the period of 2022 and from January to August 2023. This new proposal proposes the opening of a new base of CIOPAER in the Jaguaribe and Center-South region so that there is no need for aircraft to travel from Fortaleza to respond to incidents in these regions. It is also proposed to transfer the base from the municipality of Quixadá to the municipality of Quixeramobim, making the response time faster in responding to aeromedical and rescue incidents, due to the regional hospital of the central hinterland is located in the municipality of Quixeramobim and the last proposal is a new aircraft maintenance system in CIOPAER's monthly, 100-hour and 150-hour inspections.